ممارسات خدمات الصيرفة الالكترونية في البنوك الجزائرية - دراسة حالة البنك الوطني الجزائري Bna – - بن جدو, أمينة; ديقش, سمية (جامعة الوادي - University of Eloued, 2020)
This study aims to identify the most important practices of electronic banking services in the Algerian banks. To achieve this objective, the study of the status of the National Bank of Algeria (BNA) was conducted as one of the largest financial institutions nationally. It was concluded that there is an electronic banking service in the bank under study through The application of information and communication technology, and providing electronic banking channels such as ATMs in addition to providing some electronic payment methods such as electronic cards
The practice of electronic banking services in Algerian bankscase study of national bank of Algeria BNA
مقال
Keywords: الصيرفة الالكترونية ; قنوات الصيرفة الالكترونية ; وسائل الدفع الالكترونية